2014
DOI: 10.1164/rccm.201408-1492pp
|View full text |Cite
|
Sign up to set email alerts
|

Airway Basal Cells. The “Smoking Gun” of Chronic Obstructive Pulmonary Disease

Abstract: The earliest abnormality in the lung associated with smoking is hyperplasia of airway basal cells, the stem/progenitor cells of the ciliated and secretory cells that are central to pulmonary host defense. Using cell biology and 'omics technologies to assess basal cells isolated from bronchoscopic brushings of nonsmokers, smokers, and smokers with chronic obstructive pulmonary disease (COPD), compelling evidence has been provided in support of the concept that airway basal cells are central to the pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
77
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 69 publications
3
77
0
2
Order By: Relevance
“…Why smokers with underlying airflow obstruction are at greater risk of lung cancer than smokers with normal lung function remains unknown (13)(14)(15)(16). Early hypotheses suggested that patients with COPD have a greater accumulation of carcinogens in the airway (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Why smokers with underlying airflow obstruction are at greater risk of lung cancer than smokers with normal lung function remains unknown (13)(14)(15)(16). Early hypotheses suggested that patients with COPD have a greater accumulation of carcinogens in the airway (1,2).…”
mentioning
confidence: 99%
“…Other hypotheses link lung cancer with underlying emphysema and lung remodeling (13,14). The innate immune response has been implicated in both COPD and lung cancer in large prospective studies (15)(16)(17)(18). Systemic inflammation, reflecting innate immune hyperresponsiveness, has been linked to both progression of lung remodeling leading to COPD and DNA damage leading to lung cancer (18).…”
mentioning
confidence: 99%
“…Club cells, identified during the 19th century, are one of these targets and thorough efforts have aimed at identifying them as another "smoking gun" candidate [3]. CC16, a 15.8-kDa protein, is secreted by these nonciliated bronchiolar cells and is supposed to have anti-inflammatory properties.…”
mentioning
confidence: 99%
“…Smoking-associated lung diseases, such as COPD, pose an unique challenge. The basal cell population isolated from COPD patients has been reported to display an altered gene expression profile and diminished capacity for regeneration (48). While the regenerative capacity is reduced in basal cells from smokers (43), it is not a completely lost, suggesting that a regenerative subpopulation remains.…”
Section: Discussionmentioning
confidence: 99%